2021
DOI: 10.1002/mds.28545
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemia Indicates Favorable Motor Outcome in Parkinson's Disease

Abstract: Background: The interplay between glycemic control and Parkinson's disease (PD) has long been recognized but not fully understood. Objectives: To investigate the association of glycated hemoglobin (HbA1c) levels with motor and cognitive symptom progression in a prospective PD cohort. Methods: Of 244 PD patients, 17 had low HbA1c (≤30 mmol/mol), 184 were euglycemic (HbA1c 31-41 mmol/mol), 18 had high HbA1c (HbA1 ≥42 mmol/mol), and 25 had diabetes mellitus (DM). Survival analysis was applied on time until Hoehn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…4,5 In addition to prevalent diabetes, recent studies suggested that hyperglycemia, that is glycated hemoglobin (HbA1c) ≥42 mmol/mol, is an independent predictor of faster motor progression determined by Hoehn & Yahr (H&Y) stage ≥3 or Movement Disorder Society-Unified Parkinson's Disease Rating Scale Part III (MDS-UPDRS III) >4 points. 6,7 In line with these findings, a cross-sectional study revealed that high HbA1c levels in PD patients are associated with more severe motor impairment (MDS-UPDRS III). 8 Interestingly, interventional trials using antidiabetic drugs indicate that there might be a causal relationship between glycemic control and motor severity in PD patients.…”
Section: Supporting Datamentioning
confidence: 79%
See 1 more Smart Citation
“…4,5 In addition to prevalent diabetes, recent studies suggested that hyperglycemia, that is glycated hemoglobin (HbA1c) ≥42 mmol/mol, is an independent predictor of faster motor progression determined by Hoehn & Yahr (H&Y) stage ≥3 or Movement Disorder Society-Unified Parkinson's Disease Rating Scale Part III (MDS-UPDRS III) >4 points. 6,7 In line with these findings, a cross-sectional study revealed that high HbA1c levels in PD patients are associated with more severe motor impairment (MDS-UPDRS III). 8 Interestingly, interventional trials using antidiabetic drugs indicate that there might be a causal relationship between glycemic control and motor severity in PD patients.…”
Section: Supporting Datamentioning
confidence: 79%
“…Besides PD risk, prevalent diabetes was also associated with greater motor symptoms and faster motor progression in patients with PD 4,5 . In addition to prevalent diabetes, recent studies suggested that hyperglycemia, that is glycated hemoglobin (HbA1c) ≥42 mmol/mol, is an independent predictor of faster motor progression determined by Hoehn & Yahr (H&Y) stage ≥3 or Movement Disorder Society‐Unified Parkinson's Disease Rating Scale Part III (MDS‐UPDRS III) >4 points 6,7 . In line with these findings, a cross‐sectional study revealed that high HbA1c levels in PD patients are associated with more severe motor impairment (MDS‐UPDRS III) 8 .…”
mentioning
confidence: 99%
“…Markaki and colleagues showed that in nondiabetic PD patients, low and high HbA1c levels (HbA1c ≤30 mmol/mol or ≥42 mmol/mol) were associated with unfavorable motor outcome (Hoehn & Yahr stage ≥3). 3 Zittel and colleagues have also recently shown an association between increased HbA1c level (HbA1c ≥42 mmol/mol) and motor progression (MDS-UPDRS III increase of >4 points) in PD patients regardless of diabetic status. 4 In a separate study, Yang and colleagues showed that in PD patients, dysglycemia was associated with cognitive impairment.…”
mentioning
confidence: 92%
“…The cross-talk between glycometabolic derangement and inflammatory response may be important participants in PD motor and cognitive decline. In addition to aging, an increase in HbA1c levels had been shown to be associated with central dopaminergic activity decline in non-diabetic persons [ 84 , 85 , 86 ].…”
Section: The Linkage Between Dm and Pdmentioning
confidence: 99%